L’intérêt d’assurance : un élément fondamental du contrat d’assurance - Moreau, Rémi (Assurances, 1994)
In this article, the author comments on the evolution of the principle of insurable interest, first in property insurance, then in insurance of persans and finally in marine insurance. The scope, the existence and the application of such an interest could vary depending on the class of insurance. General rule lies on the fact that to be enforceable, all insurance contracts must be supported by an insurable interest; otherwise, insured could collect even though a loss has not occurred. This would be contrary not only to the public interest, but also to the mutual community of the insured. The author examines the basic principles of the 1866 Civil Code of Lower Canada, the new modifications from the Quebec Civil Code, which became effective January 1, 1994, and the changing large conceptions recently introduced by the courts.